2009
DOI: 10.1002/anie.200902575
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Allylpalladium Carboxylate Complexes: Identification of the Resting State of Catalytic Enantioselective Decarboxylative Allylic Alkylation Reactions of Ketones

Abstract: Palladium poprocks: Hold on to your CO2! Enantioselective Pd-catalyzed decarboxylative alkylation of ketone enolates proceeds via η1-σ-allyl Pd-carboxylate complexes by slow loss of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 35 publications
7
86
0
1
Order By: Relevance
“…In previous experiments, we have found that ( S )- t -Bu-PHOX will generally prefer to incorporate the allyl group from the Re face 7 ; the predicted products are shown in Scheme 7. The high enantioselectivity observed for the minor product can be explained by considering the relative amount of each product and the competing modes of control (Figure 6).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous experiments, we have found that ( S )- t -Bu-PHOX will generally prefer to incorporate the allyl group from the Re face 7 ; the predicted products are shown in Scheme 7. The high enantioselectivity observed for the minor product can be explained by considering the relative amount of each product and the competing modes of control (Figure 6).…”
Section: Resultsmentioning
confidence: 92%
“…The formation of a palladium carboxylate intermediate in our decarboxylative allylic alkylation has been supported by subsequent mechanistic studies performed by our laboratories. 7 Furthermore, the possibility that Pd(II) species formed in situ facilitate decarboxylation via Lewis acid type coordination (in a manner analogous to the Brønsted acid shown in Figure 2), can not be precluded.…”
Section: Resultsmentioning
confidence: 99%
“…In certain cases the chemical yields of the Pd-catalyzed allylic alkylation are somewhat modest. This is likely due to a combination of steric congestion and the opportunity for palladium-enolates to proceed through multiple catalytic pathways (inner sphere versus outer sphere alkylation chemistry), 22 some of which do not productively lead to the desired product (e.g., enolate protonation, 23 β-hydride elimination, 24 etc. ).…”
Section: Resultsmentioning
confidence: 99%
“…4, Scheme 1). Not surprisingly, this class of reaction has also received considerable recent attention from the organic chemistry community [37][38][39][40]. However, the concept of using metal catalysts to selectively decompose esters is not new, and dates back over a century ago to Sabatier's work on the reactions of esters with metal oxide catalysts [41].…”
Section: Introductionmentioning
confidence: 99%